2007
DOI: 10.1103/physreve.76.046306
|View full text |Cite
|
Sign up to set email alerts
|

Multiple zonal jets and drifting: Thermal convection in a rapidly rotating spherical shell compared to a quasigeostrophic model

Abstract: We demonstrate that thermal convection in a rapidly rotating spherical shell may produce zonal flows outside the tangent cylinder that consist of multiple alternating jets drifting towards the interior. A quasigeostrophic model that in model space is located between the classical annulus and the spherical shell, has been constructed. In this generalized annulus model we allow for terms in the Ekman correction to the flow that are usually neglected. It is shown that these terms may create observable effects at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Using a QG model of thermal convection, Rotvig (2007) shows that zonal jets drift inwards provided that the slope β has a significant dependence on radius, while QG models with constant β produce multiple jets that do not drift (e.g. Jones et al, 2003).…”
Section: Drift and Stability Of The Zonal Jetsmentioning
confidence: 99%
“…Using a QG model of thermal convection, Rotvig (2007) shows that zonal jets drift inwards provided that the slope β has a significant dependence on radius, while QG models with constant β produce multiple jets that do not drift (e.g. Jones et al, 2003).…”
Section: Drift and Stability Of The Zonal Jetsmentioning
confidence: 99%
“…This result relates well to Gilman (1978b) and Christensen (2001), who find only two-jet solutions outside the tangent cylinder at relatively high Ekman numbers. Rotvig (2006) demonstrated that in a three-dimensional Boussinesq shell with non-slip boundaries, imposed temperature contrast, and a ratio of 0.35 between the inner and outer radius, multi-jet solutions begin to emerge when E < 5 × −6 .…”
Section: Windows Of Multiple-jet Solutionsmentioning
confidence: 99%
“…The form of C is given by equation (2.8), but in more complex models, involving curved boundaries, compressibility and magnetic fields, the functional form of C may alter. Rotvig (2006) analyses a duct with curved top and bottom boundaries. In a simplified version of this system, β(y) and C(y) may be identified as the coefficients in front of −∂ x V and −|β| 1/2 ∇ 2 V , respectively in equation (2.6).…”
Section: Windows Of Multiple-jet Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, performing three-dimensional nonlinear simulations in spherical geometry can be computationally expensive. Quasi-geostrophic models 7,10,11 assume that the rapid rotation leads to columnar structures with little z-dependence, leading to two-dimensional models. The Busse annulus 7,[12][13][14][15] is one such quasi-geostrophic model.…”
Section: Introductionmentioning
confidence: 99%